Qualitative research across boundaries of language: The representation of lived experiences - G. Calvert (South African Family Practice)
Background: Qualitative methodology has a growing importance in primary care research, reflected in projects submitted for the degree of MFamMed at The Medical University of Southern Africa (Medunsa). These projects were completed in multilingual settings and sought highly subjective information.This paper aimed to demonstrate how researchers handled issues of language within their work.